On uniform Kadec-Klee properties and rotundity in generalized Cesàro sequence spaces - Petrot N. (2014)
We consider the generalized Cesàro sequence spaces defined by Suantai (2003) and consider it equipped with the Amemiya norm. The main purpose of this paper is to show that ces(p) equipped with the Amemiya norm is rotund and has uniform Kadec-Klee property. © Hindawi Publishing Corp.